Litanies and saint's feast: Catholic tradition of the feast of St. Francis of Assisi in the community of Curicaca (Research, Society and Development, 2023)
The article is an effort of ethnographic records of the feast of St. Francis of Assisi in the community of Curicaca in the municipality of Alenquer, Pará, which had as its objective to weave the relationships that are multifaceted in the memories of the faithful of St. Francis of Assisi, and of the Mota family, responsible for and realization of this manifestation for years. As an instrument of data collection, ethnographic research was used in order to verify the relations of faith and devotion that the community faithful deposit to the Catholic Saint. As a result, it was found that the community members give credibility to the Saint as an important symbol of respect and faith, thus deducing that they have the power of blessings, as a form of gratitude, the faithful hold parties with food, drinking, masses and the dispute of the masts.